Osteocalcin has a muscle-protective effect during weight loss in men without metabolic syndrome: a multicenter, prospective, observational study - Xiang, Yi; Lu, Wenyi; Mao, Xiaomeng; Zou, Jing; Wang, Jialu; Xu, Renying; Tang, Qingya (Frontiers in Endocrinology, 2023)
Weight reduction often accompanies muscle loss. Existing studies highlight the involvement of osteocalcin (OC) in energy metabolism and its potential to prevent age-related muscle loss. Nevertheless, these studies predominantly involve individuals with hyperglycemia, yielding conflicting research outcomes. This study investigated the protective role of OC against muscle loss during weight reduction in individuals without metabolic syndrome (MetS).We enrolled 130 overweight or obese individuals without MetS in a 4-month high-protein, energy-restricted dietary weight management program conducted at two clinic centers. Body composition and laboratory tests were assessed both before and after weight loss.Correlation and regression analysis were made between the changes in metabolic indicators and muscle mass during weight loss.Following weight loss, there was a decrease in body mass index (BMI), percentage of body fat (PBF), visceral fat area (VFA), fasting insulin (FINS), homeostasis model assessment insulin resistance (HOMA-IR), glycated haemoglobin (HbA1c), and lipid profile, and increase in the percentage of skeletal muscle (PSM) and vitamin D. There was no change in osteocalcin (OC) during the intervention. Correlation analysis of the relative changes in all metabolic indicators revealed a positive correlation between OC and PSM (r=0.383, p=0.002). Multiple linear regression analysis found that OC has a significant protective effect on muscles during weight loss in males after adjusting for confounding factors (β=0.089, p=0.017).High-protein, energy-restricted diets demonstrate efficacy in enhancing metabolic indicators within the weight-loss population. Furthermore, OC exhibits a protective effect on muscle mass during weight reduction in individuals without MetS, with this effect being particularly evident in males.